#### Question

If one root of the equation 4x^{2} − 2x + (λ − 4) = 0 be the reciprocal of the other, then λ =

8

-8

4

-4

#### Solution

Let `alpha and beta `be the roots of quadratic equation `4x^2 - 2x + (λ - 4) = 0` in such a way that `alpha = 1/beta`

Here, a = 4,b = -2 and , c= (λ - 4)

Then , according to question sum of the roots

`alpha + beta = (-b)/a`

`1/beta + beta = (-(-2))/4`

`(1+beta^2) = 1/2`

`2 + 2beta^2 = beta`

`2beta^2 - beta + 2 = 0`

And the product of the roots

`alpha . beta = c/a`

`1/beta xx beta = (λ - 4)/4`

`1 = (λ -4)/4`

`λ - 4 = 4`

`λ = 4 + 4`

`= 8`

Therefore, value of `λ = 8`.

Is there an error in this question or solution?

#### APPEARS IN

Solution If One Root of the Equation 4x2 − 2x + (λ − 4) = 0 Be the Reciprocal of the Other, Then λ = Concept: Solutions of Quadratic Equations by Factorization.